Upaya Meningkatkan Minat Dan Hasil Belajar Matematika Melalui Strategi Pembelajaran Peningkatan Kemampuan Berpikir Pada Pada Siswa Kelas IX SMP Taman Dewasa Ibu Pawiyatan Yogyakarta 2016/2017 - Yulen Karepi Muama; A.A Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
The purpose of this research is to increase the interest and the result of learning mathematics class IX Junior High School Student Class IX Smp Taman Mature Ibu Pawiyatan through Learning Strategy Improving Thinking Ability (SPPKB).The results of this study indicate that after applied Learning Strategy Model of Improving Thinking Ability (SPPKB), interest and learning achievement of mathematics have increased. Student interest increased from cycle I of 64, 79% increased to 70,81% in cycle II. While the student's learning outcomes also experienced an increase. The average value of students from the initial ability of 50.33 with 5 students (16.67%) who meet the KKM increased to 55.90 with 9 students (30.00%) who meet the KKM on cycle I. While in cycle II the average score of students increased to 78.82 with 22 0rang students (73.33%) who meet the KKM in cycle II. Thus, it is suggested that teachers in learning mathematics is suggested to use Learning Strategy Model of Improvement of Thinking Ability (SPPKB) on other materials as an alternative to increase student's interest and learning achievement.